Jurnal Penyuluhan: Perbedaan Tahapan Pembelajaran Sekolah Lapang Pengelolaan Tanaman Terpadu Padi Sawah antar Komunitas Petani di Lampung - Slameto, F. Trisakti Haryadi, Subejo (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
Enhancement of paddies production in Lampung done with implementation of agriculture technology innovation. The effort done with farmer field school of integrated crops management (FFS-ICM) of paddies. The learning of field school occured on various ethnic community of rice farmers.